Biometric parameters and choroidal microstructure in Chinese children with unilateral anisometropia - Wen, Jing; Cao, Yiwen; Zhao, Jingjing; Zhu, Dehai (Frontiers in Medicine, 2025)
PurposeThis study aimed to investigate the biological parameters and choroidal microstructure of the eyes of children with unilateral anisometropia and to analyze the factors influencing refractive development in these patients.MethodsThis observational cross-sectional study included 26 patients with unilateral hyperopic anisometropia and 34 patients with unilateral myopic anisometropia. Biometric parameters, including axial length (AL) and average keratometry (Ave-K), were measured. Choroidal thickness (CT) and vascular microstructure parameters, including the total choroidal area (TCA), luminal area (LA), stromal area (SA), and choroidal vascularity index (CVI), were obtained with enhanced depth imaging optical coherence tomography (EDI-OCT).ResultsCompared to normal eyes, the AL and AL/K ratio were significantly lower in hyperopic eyes but significantly higher in myopic eyes (all p <0.001). The TCA and LA were significantly greater in hyperopic eyes and significantly lower in myopic eyes compared to normal eyes (all p <0.005). The LA/SA ratio and CVI were significantly lower in myopic eyes (p = 0.002, p <0.001) and non-significantly greater in hyperopic eyes than in normal eyes (p = 0.072, p = 0.050). In hyperopic anisometropia, interocular differences in both the AL and AL/K ratio were negatively correlated with subfoveal choroidal thickness (AL: r = −0.529, p = 0.005; AL/K: r = −0.612, p = 0.001) and the LA (AL: r = −0.393, p = 0.047; AL/K: r = −0.407, p = 0.039).ConclusionSignificant negative correlations between axial length and choroidal parameters (subfoveal choroidal thickness [SFCT]/ and luminal area [LA]) in hyperopic anisometropia suggest that axial elongation may be associated with choroidal thinning. The CVI decreases as hyperopia progresses to emmetropia and then to myopia, indicating that choroidal vascularity changes during refractive development.